PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN INVESTIGATIF UNTUK MENINGKATKAN KEMAMPUAN PENALARAN DAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR: Indonesia - Nurhayati; Afrizawati; Yandra Rivaldo (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2021)
This study aims to develop mathematical reasoning and representation skills through learning mathematics with an investigative approach. The focus of this study is to reveal the comparison of the reasoning abilities and mathematical representation of elementary school students as a result of the application of mathematics learning with investigative and conventional approaches. The research design used was non-equivalent pretest-posttest control groups which is a quasi-experimental research model. The sample in this study were 205 fifth-grade elementary school students in the city of Tasikmalaya based on three school categories consisting of three schools in the experimental group and three schools in the control group. Based on the results of data analysis in this study, it was concluded that the investigative approach was significantly better at improving the reasoning abilities and mathematical representation of elementary school students compared to the conventional approach. Through an investigative approach, students from the low-category school group showed better mathematical reasoning and representation abilities than other groups. Meanwhile, students with high general mathematical abilities improved better than other groups.